2020
DOI: 10.21203/rs.3.rs-85918/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-Assembled Bovine Serum Albumin Nanoparticles as Pesticide Delivery Vectors for Controlling Trunk-Boring Pests

Abstract: Trunk-boring pests (TBPs) are an important type of forest pest, TBPs not only feed on the branches and trunks of trees, but also spread quarantine diseases in forests. However, because the larvae of TBPs live inside the trunk and are well concealed, prevention and control are difficult. The lack of effective control methods leads to the death of many trees in forests. In this study, a novel nanopesticide featuring high bioactivity and slow-release properties was developed to control TBPs. Thiacloprid (THI), wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The presence of rough spherical surface of NPs, indicates that rhamnolipid is present on the surface of NPs. Previously there are several reports where researchers have used desolvation method to synthesize albumin NPs in various size range (600 ± 60 nm, 13 108.6 ± 342 nm and 100 nm 43 ). However, we have got the particle size of control NPs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of rough spherical surface of NPs, indicates that rhamnolipid is present on the surface of NPs. Previously there are several reports where researchers have used desolvation method to synthesize albumin NPs in various size range (600 ± 60 nm, 13 108.6 ± 342 nm and 100 nm 43 ). However, we have got the particle size of control NPs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Protein. Proteins (such as zein, 153 soybean protein, 154 feather keratin 155 and bovine serum albumin (BSA) 156 ) have a unique spatial structure to realize drug loading, but also have good biodegradability and biocompatibility. 27 Zein nanoparticles were prepared by an antisolvent precipitation method as an ecofriendly carrier system for packaging botanical repellents geraniol (GRL) and R-citronellal (R-CTL).…”
Section: Natural Macromolecular Materialsmentioning
confidence: 99%
“…Previous studies have shown that more than 90% of pesticides applied are lost following their application 3 . Such low efficiency encourages the repeated application and abuse of pesticides, which poses major risks to the production of food and the environment 4–6 . There is thus a need to develop agrochemical products that are both efficient and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…3 Such low efficiency encourages the repeated application and abuse of pesticides, which poses major risks to the production of food and the environment. [4][5][6] There is thus a need to develop agrochemical products that are both efficient and environmentally friendly. The development of nanomaterials-based pesticide delivery systems (PDSs) and nanoformulations in recent years has provided new approaches for overcoming many of the drawbacks associated with traditional pesticide formulations.…”
Section: Introductionmentioning
confidence: 99%